Early detection of localized prostate cancer in an outpatient population with prostatism symptoms - (:unkn) unknown (My University, 1997)
The majority of prostate cancers continue to be clinically diagnosed after the tumor has spread beyond the prostate gland, decreasing curative odds considerably. The principal aim of the early diagnosis of prostate cancer(PCa) must be the detection of disease in a pathologically organ-confined status. In the present study, the results of TRUS-guided prostate biopsies in patients with prostatism symptoms who were biopsied in the presence of abnormal ORE and/or elevated PSA levels were analyzed. The total study population was comprised of 747 consecutive symptomatic males. Three hundred fifteen patients who were found to have a PSA value less than 4 mg/ml and normal DRE were included in a surveillance program, where they were followed up with annual PSA and DRE. PCa was detected in 85 (11.3% of the total) of the remaining 432 patients. Of 85 patients, clinically localized disease was found in 45 and locally advanced and metastatic disease in the remaining 40 patients. In the clinically localized group, 8 patients were included in a surveillance program, 8 patients were referred for radical radiotherapy and the remaining 29 patients were underwent radical prostatectomy. In the radical surgery group, 13 patients were found to have pT2 NO, and 16 and patients pT3 NO. In light of these results, the incidence of clinically and pathologically organ confined prostate cancer in an outpatient population with obstructive lower urinary tract symptoms are 6.0 % and 1.7%, respectively. The presence of pathologically non-organ confined PCa in 55.1%(16/29) of clinically localized disease indicates that we still face problems in the early diagnosis of PCa.